Hypocholesterolemic effects of soy protein isolates from soybeans differing in 7S and 11S globulin subunits vary in rats fed a high cholesterol diet. (December 2022) - Liu, Shanshan; Luo, Tingting; Song, Yanru; Ren, Hongbo; Qiu, Zhendong; Ma, Chongxuan; Tian, Yusu; Wu, Qi; Wang, Fu; Krishnan, Hari B.; Yu, Wenhua; Yang, Jiliang; et al.
Graphical abstract: Highlight: Genotype differ in globulin subunit compositions may affect the hypocholesterolemic effect of SPI. SPIs with different genotypes represent different hypocholesterolemic molecular mechanism. Daily ingestion of SPI-2 might contribute to increase HDL-C level in hypercholesterolemic rats. 7S(α′+α)-Null genotype provided a greater beneficial effect on increasing HDL-C level in hypercholesterolemic rats. Abstract: The objective of this study was to determine if genotypes with differing globulin subunit compositions affect the hypocholesterolemic effect (HCE) of soy protein isolates (SPIs). Six SPIs (300 mg/kg/day), which differed in the 11S/7S globulin subunit composition, and fenofibrate (FF) (30 mg/kg/day), a hypocholesterolemic drug, were administered by gavage for 28 days to hypercholesterolemic model rats (HMRs). Blood samples were collected to measure serum lipid parameters. Hepatic histopathologic and lipid biochemical data were collected, and the expression of cholesterol metabolism-related key genes was analyzed. Our results demonstrated that soybeans differing in genotype generate SPIs with marked different HCEs, and the mechanism underlying the various HCEs of SPIs is associated with differential expression of hepatic cholesterol metabolism-related key genes in HMRs. 7S(α′+α)-Null genotype provided a greater effect on increasing HDL-C level, and daily ingestion of SPI-2 (null α′, α) might significantly contribute to increase HDL-C level in HMRs.